2013
DOI: 10.1112/jlms/jdt018
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Carleson embeddings for model spaces

Abstract: The classical embedding theorem of Carleson deals with finite positive Borel measures µ on the closed unit disk for which there exists a positive constant c such that f L 2 (µ) ≤ c f H 2 for all f ∈ H 2 , the Hardy space of the unit disk. Lefèvre et al. examined measures µ for which there exists a positive constant c such that f L 2 (µ) ≥ c f H 2 for all f ∈ H 2 . The first type of inequality above was explored with H 2 replaced by one of the model spaces (ΘH 2 ) ⊥ by Aleksandrov, Baranov, Cohn, Treil, and Vol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…However, the space GK 2 I is in general neither contained in H 2 , nor closed even it it were contained in H 2 . For this we would need that |G| 2 dm is a Carleson and a reverse Carleson measure for K 2 I (the first condition guarantees that GK 2 I is a subspace of H 2 and the second one that it is closed; we refer to [13], [49], [6]).…”
Section: Kernels Of Toeplitz Operators and Extremal Functionsmentioning
confidence: 99%
“…However, the space GK 2 I is in general neither contained in H 2 , nor closed even it it were contained in H 2 . For this we would need that |G| 2 dm is a Carleson and a reverse Carleson measure for K 2 I (the first condition guarantees that GK 2 I is a subspace of H 2 and the second one that it is closed; we refer to [13], [49], [6]).…”
Section: Kernels Of Toeplitz Operators and Extremal Functionsmentioning
confidence: 99%
“…Then H (b) = (bH 2 ) ⊥ is the classical model space and is certainly a closed subspace of H 2 . There is a concept developed in [5] of a dominating set. Here a Borel set E ⊂ T with m(E) < 1 is called a dominating set for (bH 2 ) ⊥ if T |f | 2 dm E |f | 2 dm, f ∈ (bH 2 ) ⊥ .…”
Section: Final Remarkmentioning
confidence: 99%
“…In [5] it is shown that dominating sets exist for every model space (bH 2 ) ⊥ and can be used to give sufficient conditions for reverse Carleson embeddings for these spaces.…”
Section: Final Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the problem of rank one perturbations has connections to many interesting topics in analysis, such as model theory including deBranges-Rovnyak and Sz.-Nagy-Foiaş model spaces [7,17,19], Nehari interpolation [24], Carleson embeddings [5], singular integral operators [18], and truncated Toeplitz operators [4].…”
Section: Introductionmentioning
confidence: 99%